Cointegration tests of PPP: do they also exhibit erratic behaviour? - Guglielmo Maria Caporale; Christoph Hanck (Center for Economic Studies and ifo Institute (CESifo), 2006)
We analyse whether tests of PPP exhibit erratic behaviour (as previously reported by Caporale et al., 2003) even when (possibly unwarranted) homogeneity and proportionality restrictions are not imposed, and trivariate cointegration (stage-three) tests between the nominal exchange rate, domestic and foreign price levels are carried out (instead of stationarity tests on the real exchange rate, as in stage-two tests). We examine the US dollar real exchange rate vis-à-vis 21 other currencies over a period of more than a century, and find that stage-three tests produce similar results to those for stage-two tests, namely the former also behave erratically. This confirms that neither of these traditional approaches to testing for PPP can solve the issue of PPP.
Keywords: C12; C22; F31; 330